2010
DOI: 10.1002/lary.21091
|View full text |Cite
|
Sign up to set email alerts
|

The surgical management of goiter: Part II. Surgical treatment and results

Abstract: In this series of patients with extensive goiter, primary and revision surgery were associated with low rate of complications. Surgical complications were associated with bilateral and large goiters suggesting increased caution in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 18 publications
0
58
0
1
Order By: Relevance
“…Not all experts agree with this policy and Randolph et al [26] who reviewed 200 cases of large cervical and substernal goitres, report only a 1.5% recurrence rate, despite over 60% of patients being managed by unilateral thyroid lobectomy. Although analysis of this retrospective group suggested that a positive family history and female sex were predictors of recurrence, extent of surgery was not included in this multivariate analysis.…”
Section: Surgical Strategy For Multinodular Goitrementioning
confidence: 90%
See 3 more Smart Citations
“…Not all experts agree with this policy and Randolph et al [26] who reviewed 200 cases of large cervical and substernal goitres, report only a 1.5% recurrence rate, despite over 60% of patients being managed by unilateral thyroid lobectomy. Although analysis of this retrospective group suggested that a positive family history and female sex were predictors of recurrence, extent of surgery was not included in this multivariate analysis.…”
Section: Surgical Strategy For Multinodular Goitrementioning
confidence: 90%
“…In selected cases a full total lobectomy on the side of the smaller lobe, with division of the isthmus may be advisable. This will allow better mobilization of the dominant lobe, reducing cervical pressure and helping to locate the RLNs and the parathyroid glands more easily [26,28].…”
Section: Incision and Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of series failed to show cases of tracheomalacia [143,144], while a small number has been reported in others [145]. It has been postulated that this entity has been mistaken for unrecognised bilateral vocal cord paralysis [146]. Tracheomalacia is treated with intubation, tracheotomy, mesh repair of the posterior tracheal wall, trachelopexy and grafting.…”
Section: Tracheomalaciamentioning
confidence: 99%